(3GdGfJUGQs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s ((3eOjf Hf YHOGdQMef GdWHjH s)
(3ChdgG (B:s
(3bGd GdHWdjhSi(B: (3Ef Chdj eG CHJOF Hg cd PcQ hGaJJM hCMLi eG JHjf Hg ai cd CeQ hCSJfLM PcQ Gddg JYGdi QCjJ Gddg efgL GdMb hSfJg hLYdc ef GdPjf jSJeYhf Gdbhd ajJHYhf CMSfg s
(3BNQgG (B:s
(3hdG GcKQ JUMjag hJMQjag , hde jHdZ eOffG ajg hdGfUjag, hfMf fSJZaQ Gddg ef GdRdd, hfSCdg GdJhajb dUGdM GdYed, Efg GdeQLh hGdeDed, hgh MSHfG hYdjg GdJhcd s
(3GfXQ GdLRA GdChd HQbe (B402 (3COH JMJ YfhGf (B:"(3QSGdI aj GdQO(B"s
(3ESJYedJ ajgG YdGeGJ GdJQbjes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B121s
Keywords: (3GdCOHs